Mapping knowledge domain of “TRANSPORT”: a bibliometric study of its status quo and emerging trends - Zhou, Wei; Xu, Zeshui; Skačkauskas, Paulius (Transport, 2019)
Transport plays an important role in human society. Due to its significance, the research journal TRANSPORT was established with the aim of developing and reinforcing the performance of national transport system based on theoretical and empirical investigations. The analyses such as transport policy, transport system fundamentals, multiple transport methods and traffic safety are all within the research scope of TRANSPORT. Therefore, this paper focuses on learning the development of this multidisciplinary journal by using the bibliometric tools. After analysing 704 papers published from January 2007 to June 2019 on TRANSPORT, the development of this journal is comprehensively analysed from the perspectives of its status quo and emerging trends. Specifically, the current status is introduced based on the general journal information, the publication and citation number, the citation structure and the significant contributors in terms of author, journal, institution and country. As for the emerging trends, the citation burst detections and the timeline view analysis are presented to give some deep insights of the hot research streams in certain time periods. This paper makes the contribution to provide a knowledge map of the journal TRANSPORT’s research domain to help researchers learn this journal and transport-related issues clearly and directly. It can be also considered as the reference source for further investigations.